Hans-Jörg Himmel et al., incorporation of a redox-active bis(guanidine) in low-dimensional tin and lead Iodide structures: front cover - Herrmann, Hendrik Hans; Walter, Petra; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2017)
The Front Cover shows a new tin iodide material with embedded redox-active guanidine units that protect the tin atoms from being oxidized like an umbrella against a sudden downpour at the beach. The first integration of a redox-active organic molecule into such materials is the proof of principle for a new concept for increasing the stability of tin iodide materials. We thank the Bundesministerium für Bildung und Forschung (BMBF) for generous support through the “Perosol” project and our project partners for an inspiring collaboration. More information can be found in the Full Paper by H.-J. Himmel et al. For more on the story behind the cover research, see the Cover Profile.
Verfasser: Hendrik Herrmann, Petra Walter, Elisabeth Kaifer, Hans-Jörg Himmel
Gesehen am 11.08.2021